Hubungan Ketuban Pecah dengan Kejadian Asfiksia Neonatorum di RSUD Kabupaten Kediri Tahun 2016: Relationship between ruptured membranes and asphyxia neonatorum at the Kediri District Hospital in 2016 - Lestariningsih, Yanu Yufita (Jurnal Kebidanan Midwiferia, 2017)
Premature rupture of membranerevolves 5-10% from all birth. Impact a birth premature that espoused broken fetal membrane early causess 12-15% asphyxia neonatorum. The purpose of the study to determine the correlation between premature rupture of membrane with the incidence of asphyxia neonatorum. The research method used is analytic with retrospective cohort approach with independent variable of premature rupture of membrane, dependent variable asphyxia neonatorum. The study was conducted on 7 June to 12 July 2017. The population of 1519 mothers inregional public hospital of Kediri regency 2016. Sample 139 respondents, taken by simple random sampling, was analyzed by Chi Square test with a significant of 0.05. Result of research most of respondent with rupture of membrane counted 46 respondents, almost all respondents that is 82.6% gave birth baby with asphyxia. From result of Chi Square test obtained by result of p-value equal to 0.000 (<0.05), result of coefficient of contingency (C) equal to 0.639 with closeness strong relation, so H1 received H0 rejected which means there is significant relation with closeness strong between premature rupture of membrane with asphyxia neonatorum inregional public hospital of Kediri regency 2016. Relative Risk (RR) 1.65 which means the possibility of a baby experiencing asphyxia neonatorum of 1.65 times in maternal who experience premature rupture of membranes compared to mothers who did not experience premature rupture of membranes.